A comment on the oral dermal flaps of Elachistocleis Parker, 1927 (Anura: Microhylidae) larvae - Laufer, Gabriel; Pereyra, Laura C.; Akmentins, Mauricio S.; Borteiro, Claudio (Zootaxa, 2013)
The Neotropical frog genus Elachistocleis Parker consists of 17 species, most of them described in the last two decades. External morphology characters traditionally used in anuran systematics to distinguish among species, such as skin texture, dermal protuberances, cranial chests and nuptial pads, are of relative value in Elachistocleis (Pereyra et al. 2013). In addition, the majority of species descriptions do not include relevant biological data like advertisement call, osteology, and tadpole morphology. In the context of the integrative taxonomy, the availability of these data are crucial to improve our understanding of the evolution and systematic of genus Elachistocleis. Particularly, tadpole characters can be an important tool for species identification and phylogenetic reconstructions (Altig 2007; Haas 2003; McDiarmid & Altig 1999).